High-crystallinity aluminum-rich ZSM-5 molecular sieve as well as preparation method and application thereof
By adding a second aluminum source to the preparation of ZSM-5 molecular sieve and performing secondary crystallization, the problem of preparing aluminum-rich ZSM-5 molecular sieve in the prior art was solved, and a high yield and high crystallinity aluminum-rich ZSM-5 molecular sieve was achieved, which improved its catalytic performance.
Patent Information
- Application Number
- CN202311219634.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-20
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2043-09-20
AI Technical Summary
It is difficult to prepare high yield and high crystallinity aluminum-rich ZSM-5 molecular sieves, and the desilicate and aluminum supplementation under high alkalinity conditions have problems such as low crystallization activity and poor uniformity.
By adding a second aluminum source during the preparation of ZSM-5 molecular sieve and performing secondary crystallization, the composition distribution of the skeleton silicon-aluminum atoms is regulated, breaking through the existing Si/Al ratio range, and improving the activity and crystallinity of the aluminum source.
The preparation of high-crystalline aluminum-rich ZSM-5 molecular sieve was achieved, which improved its acid strength, micropore diffusion, mass transfer and reaction performance, and solved the problems of low yield and low crystallinity.
Smart Images

Figure CN119683645A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of ZSM-5 molecular sieve preparation, and more specifically, to a high-crystallinity aluminum-rich ZSM-5 molecular sieve and a preparation method and application thereof. Background Art
[0002] ZSM-5 molecular sieve is a high-silicon zeolite molecular sieve with a unique pore structure developed by researchers at Mobil Corporation in the United States in the 1970s. It was soon put into industrial application as a catalytic material. It has the advantages of high thermal stability, high specific surface area, and excellent adsorption capacity for aromatic molecules. The artificial synthesis of ZSM-5 molecular sieve is of epoch-making significance and has set off a revolution in the fields of petrochemicals and catalysis. ZSM-5 molecular sieve is a type of catalytic material with great application value due to its unique pore structure and acid properties. ZSM-5 molecular sieve usually has more medium-strong acid active centers and contains higher / Lewis acid center ratio, which is conducive to the electrophilic activation of benzene rings and the formation of carbon cations, and has shown high catalytic activity and stability in catalyzing hydrocarbon reactions. At present, ZSM-5 molecular sieves have been industrially applied in aromatic conversion reactions such as toluene disproportionation, and have also been widely studied in petrochemical applications such as methanol to hydrocarbons, methane aromatization (MDA), alkyl transfer, alkyl isomerization, and can be used in catalytic reactions such as light-weighting of heavy oils, light-weighting of polycyclic aromatic hydrocarbons, and xylene isomerization.
[0003] The catalytic active centers of molecular sieves are affected by many factors. It is generally believed that the framework composition of ZSM-5 molecular sieves is closely related to their structure and surface properties. The number of active centers is generally proportional to the content of aluminum atoms in the framework. In particular, the quantitative information of the framework crystallographic T site and the coordination chemical environment largely determine the type and properties of the catalytically active solid acid center. Therefore, for catalytic reactions that require a high density of acid centers, the more Al species in the framework, the more favorable the catalytic reaction. Developing a framework aluminum-rich (low silicon) ZSM-5 material and improving its crystallinity are key technical problems that need to be solved to promote efficient catalytic applications.
[0004] The tetrapropylammonium ion (quaternary ammonium base or quaternary ammonium salt) system is the key to the ideal OSDA (organic structure directing agent) chemical environment for the efficient artificial synthesis of high-crystallinity ZSM-5. However, in the OSDA system with lower charge density, the atomic bonding activation ability is strongly affected by factors such as pH value, and the high-aluminum raw material composition cannot be activated evenly and effectively. The synthesis system containing organic templates can usually only obtain ZSM-5 molecular sieves with Si / Al>10. The effect of mixing the gel chemistry of the mixture on broadening the silicon-aluminum ratio range of the above molecular sieve products is limited, and the yield and crystallinity are easily affected by the aluminum-rich composition. At the same time, the controllability of the control means such as additives is poor, and it is difficult to achieve stable industrial production. On the other hand, based on the Pauling electrostatic valence rule and the Loewenstein rule, the synthesis of aluminum-rich frameworks requires stronger alkalinity and more balanced framework cations. In the publicly reported literature so far, even in the inorganic cation system with high charge density, it is still difficult to directly synthesize aluminum-rich molecular sieves with Si / Al<10. Moreover, the synthesis system is limited by the high nucleation activation energy, which is extremely unfavorable for the crystallization of molecular sieves. The crystallinity of molecular sieve products is much lower than that of products synthesized in the organic structure directing agent (OSDA) system. Not only is there a problem of low yield, but also due to the lack of organic structure directing agent (OSDA), it is very easy to generate small pore aluminum-rich zeolite impurities such as SOD, GIS, and ANA, which is very unfavorable for the synthesis of ZSM-5 molecular sieves. At the same time, the synthesis by seed method or directing agent method cannot fundamentally improve the above problems.
[0005] In summary, due to the limitations of the effective activation of aluminum atoms in an aluminum-rich composition environment, and the limitations of stability factors such as the bond angle and bond energy of the aluminum-containing skeleton, the in situ direct synthesis of aluminum-rich molecular sieves with Si / Al<10 is a recognized problem in the research and industrial communities, and is a key technical challenge that needs to be urgently solved in the application of efficient solid acid catalysis. If the problems of high yield and high crystallinity can be solved at the same time, the aluminum content in the skeleton can be significantly increased, providing more abundant active acid catalytic centers, which will have great prospects for industrial application. Summary of the invention
[0006] The purpose of the present invention is to provide a high-crystallinity aluminum-rich ZSM-5 molecular sieve and a preparation method thereof, so as to solve the technical problem that it is difficult to prepare high-yield, high-crystallinity aluminum-rich ZSM-5 molecular sieve in the prior art.
[0007] To achieve the above object, the technical solution adopted by the present invention is:
[0008] In a first aspect, the present invention provides a ZSM-5 molecular sieve, wherein Si / Al of the ZSM-5 molecular sieve is less than 10 and the relative crystallinity is greater than 80%.
[0009] It should be noted that Si / Al used in the present invention represents the molar ratio of Si element to Al element.
[0010] According to some embodiments of the present invention, the acid strength of the ZSM-5 molecular sieve is shown as programmed temperature ammonia desorption (NH 3 The desorption peak temperature of -TPD is 360~500℃.
[0011] In order to understand the acidity of solid acid catalysis, the temperature-programmed desorption of ammonia (NH 3 -TPD) is used for characterization. For example, it can be measured on an Altamira AMI-3300 chemical adsorption instrument produced by Micrometrics Instruments, Inc., USA. The obtained programmed temperature ammonia desorption curve has characteristic peaks at different desorption temperatures, which correspond to different acid strengths. The higher the desorption temperature corresponding to the characteristic peak, the greater the acid strength.
[0012] According to some embodiments of the present invention, in the ZSM-5 molecular sieve, the content of framework aluminum accounts for more than 80 wt% of the total aluminum.
[0013] According to some embodiments of the present invention, in the ZSM-5 molecular sieve, the content of framework aluminum accounts for more than 85 wt% of the total aluminum.
[0014] According to some embodiments of the present invention, the specific surface area S of the ZSM-5 molecular sieve is BET ≥350m 2 / g, micropore volume V micro >0.15cm 3 / g.
[0015] According to some embodiments of the present invention, the specific surface area S of the ZSM-5 molecular sieve is BET 390~500m 2 / g, micropore volume V micro 0.17~0.25cm 3 / g.
[0016] According to some embodiments of the present invention, the specific surface area S of the ZSM-5 molecular sieve is BET 425~467m 2 / g, micropore volume V micro 0.19~0.23cm 3 / g.
[0017] The ZSM-5 molecular sieve provided by the present invention breaks through the existing silicon-aluminum ratio by regulating the distribution of the silicon-aluminum atomic composition of the skeleton, has the characteristics of high acid strength and good crystallinity, and realizes the improvement of the micropore diffusion, mass transfer and reaction performance of the ZSM-5 molecular sieve.
[0018] In a second aspect, the present invention provides a method for preparing a ZSM-5 molecular sieve, comprising:
[0019] S1. Obtaining a colloid comprising a silicon source, a first aluminum source, an alkali source, a template R and a solvent I; the molar ratio of the silicon element in the silicon source to the aluminum element in the first aluminum source is greater than 10, preferably greater than 15;
[0020] S2. crystallizing the colloid obtained in step S1 to obtain a slurry;
[0021] S3. Adding a second aluminum source to the slurry obtained in step S2 so that the molar ratio of silicon to aluminum in the entire reaction system is less than 10;
[0022] S4. Performing secondary crystallization to obtain the ZSM-5 molecular sieve;
[0023] Optionally, the method further comprises S5. calcining the ZSM-5 molecular sieve once, then performing ion exchange, and then performing a second calcination.
[0024] The preparation method of the ZSM-5 molecular sieve provided by the present invention comprises the following steps: firstly mixing a first aluminum source, an alkali source, a silicon source, a template agent and a solvent I, and obtaining a high-crystallization ZSM-5 molecular sieve through a primary crystallization according to a conventional ratio of Si / Al>10, and then adding a second aluminum source, and then obtaining the ZSM-5 molecular sieve through a secondary crystallization by strengthening the atomic coordination and bonding ability. Among them, the raw material composition and the selection of conditions in the primary crystallization and the addition of the second aluminum source have an important influence on the crystallization degree of the aluminum-rich ZSM-5 molecular sieve. By optimizing the synthesis ratio and process, the activity of the aluminum source is improved, and the crystallization degree of the molecular sieve can be improved.
[0025] According to some embodiments of the present invention, in step S3, while adding the second aluminum source to the slurry obtained in step S2, it can be determined whether it is necessary to supplement an appropriate amount of solvent I according to the state of the slurry. Whether it is necessary to supplement solvent I and the specific amount of the supplementary solvent I are easily known to those skilled in the art.
[0026] According to some embodiments of the present invention, the first aluminum source and the second aluminum source are the same or different, and are each independently selected from at least one of aluminum hydroxide, aluminum isopropoxide, aluminum sec-butoxide, sodium aluminate, aluminum sulfate, aluminum nitrate, aluminum chloride, and aluminum oxide.
[0027] According to some embodiments of the present invention, the second aluminum source is selected from at least one of aluminum isopropoxide, aluminum sec-butoxide, sodium aluminate, aluminum sulfate, aluminum nitrate, and aluminum chloride.
[0028] According to some embodiments of the present invention, the alkali source includes alkali metal hydroxide and / or ammonia water; preferably, the alkali metal includes at least one of Li, Na, K, Rb, and Cs.
[0029] According to some embodiments of the present invention, the silicon source includes at least one of silicon powder, silicon balls, silica gel, silica sol, sodium silicate (sodium silicate / water glass), silica alumina, silicates (such as methyl silicate, ethyl silicate, propyl silicate, etc.), silicon tetrachloride, silane, white carbon black, and diatomaceous earth.
[0030] According to some embodiments of the present invention, the silicon source is selected from tetramethylsilane (Si(CH 3 ) 4 ), methyltrimethoxysilane (MTMS), isobutylene triethoxysilane, trichlorosilane (SiHCl 3 ) and tetraethoxysilane (Si(OC 2 H 5 ) 4 ) at least one of.
[0031] According to some embodiments of the present invention, the template R includes at least one of ammonia water, piperidine, N,N,N-trimethyl-1-adamantyl ammonium bromide, pyridine, cyclopropylamine, ethylamine, diethylamine, triethylamine, propylamine, dipropylamine, tripropylamine, n-butylamine, tetrapropylammonium hydroxide, tetraethylammonium hydroxide, tetramethylammonium hydroxide, tetrapropylammonium iodide, tetrapropylammonium bromide, tetraethylammonium bromide, tetraethylammonium chloride or tetramethylammonium chloride.
[0032] According to some embodiments of the present invention, the solvent I includes at least one of deionized water, an alcohol solvent, and an imidazole-type ionic liquid.
[0033] According to some embodiments of the present invention, the solvent I includes at least one of deionized water, methanol, ethanol, isopropanol, ethylene glycol, glycerol, acetone, and n-butanol.
[0034] According to some embodiments of the present invention, the molar ratio of the alkali source to the silicon element in the silicon source is: OH - / Si=0.01 to 0.45, for example, 0.01, 0.02, 0.03, 0.05, 0.07, 0.08, 0.10, 0.11, 0.12, 0.15, 0.18, 0.20, 0.23, 0.25, 0.30, 0.31, 0.34, 0.35, 0.36, 0.40, 0.41, 0.45, etc.
[0035] According to some embodiments of the present invention, the molar ratio of the solvent I to the silicon element in the silicon source is: I / Si=5-50, for example, it can be 5, 6, 8, 10, 13, 15, 16, 19, 20, 23, 25, 26, 28, 30, 35, 38, 40, 44, 46, 50, etc.
[0036] According to some embodiments of the present invention, the molar ratio of the template R to the silicon element in the silicon source is: R / Si=0.001-0.55, for example, it can be 0.001, 0.002, 0.005, 0.007, 0.01, 0.02, 0.04, 0.05, 0.07, 0.08, 0.10, 0.11, 0.13, 0.15, 0.20, 0.25, 0.28, 0.30, 0.35, 0.37, 0.40, 0.42, 0.43, 0.48, 0.50, 0.52, 0.55, etc.
[0037] According to some embodiments of the invention, the ion exchange comprises ammonium exchange.
[0038] According to some embodiments of the present invention, the ammonium exchange reagent includes at least one of ammonium nitrate, ammonium chloride, ammonium oxalate, and ammonium sulfate.
[0039] According to some embodiments of the present invention, the ammonium exchange is carried out at a temperature of 10 to 120° C. for 0.1 to 1000 h, preferably at a temperature of 50 to 80° C. for 0.5 to 5 h.
[0040] According to some embodiments of the present invention, the concentration of the aqueous solution of the ammonium exchange reagent is 0.01 to 5 mol / L.
[0041] According to some embodiments of the present invention, the volume mass ratio of the aqueous solution of the ammonium exchange reagent to the ZSM-5 molecular sieve is 4-10 mL: 1 g.
[0042] According to some embodiments of the present invention, the number of ion exchanges is 1 to 20 times, preferably 2 to 6 times.
[0043] According to some embodiments of the present invention, after the ion exchange, filtering, washing and drying are first performed, and then a secondary calcination is performed; preferably, the drying temperature is 30 to 200° C., preferably 80 to 120° C., and the time is 0.1 to 1000 h, preferably 0.5 to 10 h.
[0044] According to some embodiments of the present invention, the stirring speed of the primary crystallization is 0-6000 rpm, preferably 10-100 rpm, the crystallization temperature is 80-200° C., preferably 120-180° C., and the crystallization time is 2-2000 hours, preferably 100-300 hours.
[0045] According to some embodiments of the present invention, pre-crystallization is performed before the primary crystallization, and the pre-crystallization temperature is 70 to 140° C. and the time is 2 to 10 hours.
[0046] According to some embodiments of the present invention, the stirring speed of the secondary crystallization is 0-6000 rpm, preferably 10-100 rpm, the crystallization temperature is 80-200° C., preferably 120-180° C., and the crystallization time is 2-2000 hours, preferably 100-300 hours.
[0047] According to some embodiments of the present invention, pre-crystallization is performed before the secondary crystallization, and the pre-crystallization temperature is 70 to 140° C. and the time is 2 to 10 hours.
[0048] According to some embodiments of the present invention, after the secondary crystallization, filtering, washing and drying steps are further included; preferably, the drying temperature is 30 to 200° C., preferably 80 to 120° C., and the drying time is 0.1 to 1000 h, preferably 0.5 to 10 h.
[0049] According to some embodiments of the present invention, the primary calcination temperature is 200-980° C., preferably 400-650° C., more preferably 500-550° C.; the primary calcination time is 0.1-250 h, preferably 1-10 h.
[0050] According to some embodiments of the present invention, the temperature of the secondary calcination is 400-650° C., preferably 500-550° C.; the time of the secondary calcination is 1-10 h.
[0051] According to some embodiments of the present invention, the secondary calcination is carried out in a staged calcination manner, including: calcining at a temperature of 150-200°C for 0.5-3h, then calcining at a temperature of 250-350°C for 0.5-3h, then calcining at a temperature of 400-500°C for 0.5-3h, and finally calcining at a temperature of 200-900°C for 0.1-100h.
[0052] In a third aspect, the present invention provides a ZSM-5 molecular sieve prepared by the preparation method described in the second aspect.
[0053] In a fourth aspect, the present invention provides use of the ZSM-5 molecular sieve described in the first aspect or the ZSM-5 molecular sieve described in the third aspect in aromatic hydrocarbon conversion.
[0054] According to some embodiments of the present invention, the weight space velocity of aromatics in the aromatics conversion is 0.01 to 50 h -1 , the hydrogen-to-oil molar ratio is 0-300.
[0055] The ZSM-5 molecular sieve provided by the present invention is a solid acid catalytic material with a unique structure, has the characteristics of high crystallinity and aluminum-richness, has a large specific surface area and external surface active centers with high acid density, exhibits very excellent adsorption and catalytic performance for aromatic molecules, can provide more acid sites for aromatic conversion, and is used for catalyzing aromatic conversion with the characteristics of high selectivity, high activity and high stability.
[0056] According to some embodiments of the present invention, the application includes application in an aromatic hydrocarbon dealkylation reaction, such as application in a trimethylbenzene selective dealkylation reaction.
[0057] According to some embodiments of the present invention, the temperature of the trimethylbenzene selective dealkylation reaction is 250-650° C. and the pressure is 0-20 MPa.
[0058] In a fifth aspect, the present invention provides an aromatic hydrocarbon conversion catalyst, wherein the catalyst comprises the ZSM-5 molecular sieve described in the first aspect or the ZSM-5 molecular sieve described in the third aspect.
[0059] According to some embodiments of the present invention, the catalyst further comprises an active component.
[0060] According to some embodiments of the present invention, the active component includes at least one of Group IIIA alumina metals, Group IVA metals, Group VA metals, transition metals (including Groups IB to VIIB metals, and Group VIII metals).
[0061] According to some embodiments of the present invention, the active component is selected from at least one of Y, La, Ce, Pr, Nd, Fe, Co, and Ni.
[0062] According to some embodiments of the present invention, the catalyst comprises a reduction step prior to the reaction.
[0063] According to some embodiments of the present invention, the reduction is carried out by hydrogen reduction, wherein the hydrogen flow rate is 8 to 800 mL / min; during the reduction, the temperature is first increased to 100 to 280°C at a rate of 0.1 to 20°C / min and kept constant at this temperature for 0 to 48 hours, and then the temperature is increased to 300 to 750°C at a rate of 0.1 to 50°C / min and kept constant at this temperature for 0 to 48 hours.
[0064] The beneficial effects of the present invention are at least:
[0065] The preparation method of the ZSM-5 molecular sieve provided by the present invention realizes the control of the framework composition of the ZSM-5 molecular sieve by adding a second aluminum source and then undergoing secondary crystallization, thereby solving the technical bottleneck of being difficult to directly synthesize aluminum-rich ZSM-5 with high crystallinity and high yield, expanding the bond length and bond angle range that can be constructed by the aluminum-rich framework, optimizing the framework bending force constant, enhancing the framework flexibility, reducing the structural stress and achieving the coordination stabilization effect, solving the difficult problems of low crystallization activity and poor uniformity in desiliconization and aluminum supplementation under high alkalinity conditions, breaking through the lower limit of the Si / Al ratio phase region of the artificial in-situ synthesized molecular sieve, effectively controlling the crystal parameters and improving the product yield, realizing the precise construction of aluminum-rich ZSM-5 molecular sieve with high crystallinity, thereby enhancing the microporous crystallinity of the molecular sieve, optimizing its acid distribution, greatly enriching the metastable surface active acid center distribution of the molecular sieve, and having good aromatics conversion performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0066] Figure 1 The XRD spectrum of the high crystallinity aluminum-rich ZSM-5 molecular sieve prepared in Example 1 of the present invention;
[0067] Figure 2 This is a SEM photo of the high crystallinity aluminum-rich ZSM-5 molecular sieve prepared in Example 1 of the present invention;
[0068] Figure 3 This is a HR-TEM photograph of the high crystallinity aluminum-rich ZSM-5 molecular sieve prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0069] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain this patent in detail and do not limit the scope of protection of the present invention in any way.
[0070] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the raw materials, instruments and equipment used in the following examples, etc., can all be purchased on the market or can be obtained by existing methods; the reagent amounts, unless otherwise specified, are the reagent amounts used in conventional experimental operations; the experimental methods, unless otherwise specified, are all conventional methods.
[0071] In each embodiment and comparative example of the present invention, each performance data is tested according to the following test method:
[0072] (1) Phase analysis (XRD spectrum): measured using a Bruker D8Focus diffractometer with a graphite monochromator, a Cu target Kα ray source, a wavelength λ of 0.154 nm, a tube voltage of 40 kV, a tube current of 40 mA, and recording diffraction signals in the 2θ range of 3-90° (scanning speed of 2° / min).
[0073] (2) Scanning electron imaging (SEM) images: taken using a FEI Nova Nano SEM 450 microscope.
[0074] (3) Spherical aberration transmission imaging (TEM) photos: taken using a FEI Tecnai 20S-Twin microscope.
[0075] (4) Ammonia temperature programmed desorption (NH 3 -TPD) curve signal information was collected using Altamira AMI-3300 chemical adsorption instrument produced by Micrometrics.
[0076] (5) The molecular sieve samples were analyzed by low temperature N using the 3Flex-Physisorption analyzer produced by Micrometrics. 2 Adsorption-desorption characterization, the test temperature is 77K, and the specific surface area and pore structure parameters are calculated by analyzing the isotherms using the BET method and the BJH method respectively.
[0077] (6) Silicon-to-aluminum ratio of test samples: The test samples were dissolved in HF aqueous solution at room temperature and then quantitatively analyzed on an Optima 3300DV inductively coupled plasma emission spectrometer (ICP) from PerkinElmer, USA.
[0078] (7) 27 Al MAS NMR test: carried out on a VARIAN VNMRS-400WB nuclear magnetic resonance instrument, with a measurement frequency of 104.18 MHz, a rotation speed of 10000 r / s, a relaxation time of 4 s, and KAl(SO 4 ) 2 12H 2 O is a standard substance, the chemical shift signal peak of ∼60 ppm corresponds to tetracoordinated framework aluminum, and the chemical shift signal peak of ∼0 ppm corresponds to hexacoordinated non-framework aluminum.
[0079] In each embodiment and comparative example of the present invention, the polytetrafluoroethylene-lined pressure steel autoclave used was purchased from Shandong Yantai Muping Shuguang Precision Instrument Factory, with a specification of 100 mL; the rotary oven was purchased from a 200L space rotary oven produced by Beijing Creaser Company.
[0080] Example 1
[0081] A high crystallinity aluminum-rich ZSM-5 molecular sieve, the synthesis method is as follows:
[0082] First, NaOH and sodium aluminate are dissolved in deionized water, then the silicon source tetraethoxysilane is added, and finally a 25wt% aqueous solution of tetrapropylammonium hydroxide (template R) is added, wherein the silicon source (in terms of Si content), template R, aluminum source (in terms of Al content), alkali source (in terms of OH - The molar ratio of 2-nitropropene (2-nitropropene) and deionized water is 40:5:2:1.2:2000, and a milky white gel solution is obtained after being stirred evenly; the gel solution is then placed in a polytetrafluoroethylene-lined pressure steel autoclave, pre-crystallized for 6 hours at a temperature of 90°C, and then placed in a rotary oven at a temperature of 150°C and a rotation speed of 20 rpm for further hydrothermal crystallization for 160 hours, and then cooled to room temperature with tap water to obtain a slurry;
[0083] Add appropriate amount of sodium aluminate and deionized water to the slurry to make the silicon source (in terms of Si content), template R, aluminum source (in terms of Al content), alkali source (in terms of OH content) in the reaction system - The molar ratio of iodine (calculated) and deionized water is 40:5:4.5:1.2:2460; the above crystallization procedure is repeated for secondary crystallization, and tap water is used to cool to room temperature. The obtained product is filtered, washed, and dried in an oven at 100°C for 2h to obtain the original molecular sieve powder.
[0084] The molecular sieve raw powder was tested, among which the XRD test was shown in Figure 1 It can be seen that it is a pure phase MFI configuration with a relative crystallinity of 90%. SEM and TEM photos are shown in Figure 2 and Figure 3 The obtained aluminum-rich MFI topological structure ZSM-5 molecular sieve sample showed a nano-agglomeration morphology, and the individual crystals were relatively clear as a whole. The lattice fringes of the highly dispersed sample were clear from the transmission electron microscope, indicating that the microporous crystallinity of the sample was good. 27 The Al MAS NMR results show that 86wt% of the aluminum species are in a four-coordinated state. The Si / Al ratio of this sample is 8.9, and the specific surface area S BET 448m 2 / g, micropore volume V micro 0.21cm 3 / g.
[0085] The molecular sieve raw powder was calcined at 550°C for 2h and then cooled, and then the molecular sieve raw powder was subjected to ion exchange and secondary calcination. Specifically, the calcined molecular sieve raw powder and 1 mol / L ammonium chloride aqueous solution were mixed at a solid (mass, g) to liquid (volume, mL) ratio of 1:6, and heated in a water bath to 65°C for 1h for ion exchange; then filtered and washed with deionized water, and the above process was repeated 4 times to obtain a filter cake, which was dried in an oven at 100°C for 2h to obtain NH 4 + The molecular sieve was calcined at 520℃ for 3h to obtain the hydrogen type molecular sieve, which was recorded as AZ1. 3 -TPD curve shows that the desorption peak temperature of the sample is 393℃.
[0086] Example 2
[0087] A high crystallinity aluminum-rich ZSM-5 molecular sieve, the synthesis method is as follows:
[0088] First, KOH and ammonia (K + :NH4 + 2) and aluminum isopropoxide are dissolved in deionized water, followed by adding silicon source trichlorosilane, and finally adding 25wt% tetrapropylammonium bromide (template R) aqueous solution, wherein the silicon source (in terms of Si content), template R, aluminum source (in terms of Al content), alkali source (in terms of OH content) - The molar ratio of 2-nitropropene (2-nitropropene) and deionized water is 46:5:2:5:1250, and a milky white gel solution is obtained after being stirred evenly; the gel solution is then placed in a polytetrafluoroethylene-lined pressure steel autoclave, pre-crystallized for 6 hours at a temperature of 90°C, and then placed in a rotary oven at a temperature of 150°C and a rotation speed of 20 rpm for further hydrothermal crystallization for 160 hours, and then cooled to room temperature with tap water to obtain a slurry;
[0089] Add appropriate amount of aluminum nitrate and deionized water to the slurry to make the silicon source (in terms of Si content), template R, aluminum source (in terms of Al content), alkali source (in terms of OH content) in the reaction system - The molar ratio of 2-nitrogen (methylenediamine) and deionized water is 46:5:5.5:5:1480; the above crystallization procedure is repeated for secondary crystallization, and the product is cooled to room temperature with tap water. The obtained product is filtered, washed, and dried in an oven at 100°C for 2h to obtain molecular sieve raw powder.
[0090] The molecular sieve raw powder was tested, and the XRD test results showed that the obtained sample was a pure phase MFI configuration with a relative crystallinity of 87%. SEM and TEM photos showed that the sample exhibited good microporous crystallinity. 27 The Al MAS NMR results show that 92wt% of the aluminum species are in a tetracoordinated state. The Si / Al ratio of this sample is 8.5, and the specific surface area SBET 438m 2 / g, micropore volume V micro 0.20cm 3 / g.
[0091] The molecular sieve raw powder was calcined at 520℃ for 4h and then cooled, and then the molecular sieve raw powder was subjected to ion exchange and secondary calcination. Specifically, the calcined molecular sieve raw powder and 1 mol / L ammonium chloride aqueous solution were mixed at a solid (mass, g) to liquid (volume, mL) ratio of 1:6, and heated in a water bath to 65℃ for 1h for ion exchange; then filtered and washed with deionized water, and the above process was repeated 4 times to obtain a filter cake, which was dried in an oven at 100℃ for 2h to obtain NH 4 + The molecular sieve was calcined at 520℃ for 3h to obtain the hydrogen type molecular sieve, which was recorded as AZ2. 3 -TPD curve shows that the desorption peak temperature of the sample is 405℃.
[0092] Example 3
[0093] A high crystallinity aluminum-rich ZSM-5 molecular sieve, the synthesis method is as follows:
[0094] First, CsOH and aluminum isopropoxide were dissolved in deionized water, followed by the addition of silicon source methyltrimethoxysilane, and finally a 25 wt% aqueous solution of tetrapropylammonium bromide (template R), wherein the silicon source (in terms of Si content), template R, aluminum source (in terms of Al content), alkali source (in terms of OH content) - The molar ratio of 2-nitropropene (2-nitropropene) and deionized water is 40:5:2:2.4:1300, and a milky white gel solution is obtained after being stirred evenly; the gel solution is then placed in a polytetrafluoroethylene-lined pressure steel autoclave, pre-crystallized for 6 hours at a temperature of 90°C, and then placed in a rotary oven at a temperature of 150°C and a rotation speed of 20rpm for further hydrothermal crystallization for 160 hours, and then cooled to room temperature with tap water to obtain a slurry;
[0095] Add appropriate amount of aluminum chloride and deionized water to the slurry to make the silicon source (in terms of Si content), template R, aluminum source (in terms of Al content), alkali source (in terms of OH content) in the reaction system - The molar ratio of iodine (calculated) and deionized water is 40:5:4.4:2.4:1400; the above crystallization procedure is repeated for secondary crystallization, and the product is cooled to room temperature with tap water. The obtained product is filtered, washed, and dried in an oven at 100°C for 2h to obtain the original molecular sieve powder.
[0096] The original molecular sieve powder was tested, wherein the XRD test results showed that the obtained sample was a pure phase MFI configuration, and the relative crystallinity reached 85%. The SEM and TEM photos showed that the aluminum-rich ZSM-5 molecular sieve sample exhibited good microporous crystallinity. 27 The Al MAS NMR results show that 91wt% of the aluminum species are in a four-coordinated state. The Si / Al ratio of this sample is 9.8, and the specific surface area S BET 467m 2 / g, micropore volume V micro 0.23cm 3 / g.
[0097] The molecular sieve raw powder was calcined at 550°C for 2h and then cooled, and then the molecular sieve raw powder was subjected to ion exchange and secondary calcination. Specifically, the calcined molecular sieve raw powder and 1 mol / L ammonium chloride aqueous solution were mixed at a solid (mass, g) to liquid (volume, mL) ratio of 1:6, and heated in a water bath to 65°C for 1h for ion exchange; then filtered and washed with deionized water, and the above process was repeated 4 times to obtain a filter cake, which was dried in an oven at 100°C for 2h to obtain NH 4 + The molecular sieve was calcined at 520℃ for 3h to obtain the hydrogen type molecular sieve, which was recorded as AZ3. 3 -TPD curve shows that the desorption peak temperature of the sample is 365℃.
[0098] Example 4
[0099] A high crystallinity aluminum-rich ZSM-5 molecular sieve, the synthesis method is as follows:
[0100] First, RbOH and ammonia (Rb + :NH 4 + Molar ratio 1) and aluminum sec-butoxide are dissolved in deionized water, followed by adding silicon source isobutylene triethoxysilane, and finally adding n-butylammonium (template agent R), wherein the silicon source (in terms of Si content), template agent R, aluminum source (in terms of Al content), alkali source (in terms of OH content) - The molar ratio of 2-nitropropene (2-nitropropene) and deionized water is 40:4:2.5:1.4:1200, and a milky white gel solution is obtained after being stirred evenly; the gel solution is then placed in a polytetrafluoroethylene-lined pressure steel autoclave, pre-crystallized for 6 hours at a temperature of 90°C, and then placed in a rotary oven at a temperature of 150°C and a rotation speed of 20 rpm for further hydrothermal crystallization for 160 hours, and then cooled to room temperature with tap water to obtain a slurry;
[0101] Add appropriate amount of sodium aluminate and deionized water to the slurry to make the silicon source (in terms of Si content), template R, aluminum source (in terms of Al content), alkali source (in terms of OH content) in the reaction system -The molar ratio of iodine (calculated) and deionized water is 40:4:6:1.4:1450; the above crystallization procedure is repeated for secondary crystallization, and tap water is used to cool to room temperature. The obtained product is filtered, washed, and dried in an oven at 100°C for 2h to obtain the original molecular sieve powder.
[0102] The original molecular sieve powder was tested, wherein the XRD test results showed that the obtained sample was a pure phase MFI configuration, and the relative crystallinity reached 82%. The SEM and TEM photos showed that the aluminum-rich ZSM-5 molecular sieve sample exhibited good microporous crystallinity. 27 The Al MAS NMR results show that 87wt% of the aluminum species are in a four-coordinated state. The Si / Al ratio of this sample is 7.3, and the specific surface area S BET 425m 2 / g, micropore volume V micro 0.19cm 3 / g.
[0103] The molecular sieve raw powder was calcined at 500°C for 5.5h and then cooled, and then the molecular sieve raw powder was subjected to ion exchange and secondary calcination. Specifically, the calcined molecular sieve raw powder and 1 mol / L ammonium chloride aqueous solution were mixed at a solid (mass, g) to liquid (volume, mL) ratio of 1:6, and heated in a water bath to 65°C for 1h for ion exchange; then filtered and washed with deionized water, and the above process was repeated 4 times to obtain a filter cake, which was dried in an oven at 100°C for 2h to obtain NH 4 + The molecular sieve was calcined at 520℃ for 3h to obtain the hydrogen type molecular sieve, which was recorded as AZ4. 3 -TPD curve shows that the desorption peak temperature of the sample is 495℃.
[0104] Example 5
[0105] A high-crystallinity aluminum-rich ZSM-5 molecular sieve, the synthesis method of which is referred to Example 1, the only difference being that the sodium aluminate added to the slurry is replaced by an equimolar amount (calculated as Al element) of aluminum hydroxide.
[0106] The obtained molecular sieve raw powder was tested, wherein the XRD test results showed that the obtained sample was a pure phase MFI configuration, and the relative crystallinity reached 83%. SEM photos and TEM photos showed that the aluminum-rich ZSM-5 molecular sieve sample exhibited good microporous crystallinity. 27 The Al MAS NMR results show that 83wt% of the aluminum species are in a four-coordinated state. The Si / Al ratio of this sample is 9.9, and the specific surface area S BET 397m 2 / g, micropore volume V micro 0.18cm 3 / g.
[0107] The prepared molecular sieve is recorded as AZ5. 3 -TPD curve shows that the desorption peak temperature of the sample is 425℃.
[0108] Example 6
[0109] A high crystallinity aluminum-rich ZSM-5 molecular sieve, a high crystallinity aluminum-rich ZSM-5 molecular sieve, the synthesis method of which refers to Example 2, the only difference is that the aluminum nitrate added to the slurry is replaced by an equimolar amount (calculated as Al element) of aluminum oxide.
[0110] The obtained molecular sieve raw powder was tested, wherein the XRD test results showed that the obtained sample was a pure phase MFI configuration, and the relative crystallinity reached 80%. The SEM and TEM photos showed that the aluminum-rich ZSM-5 molecular sieve sample exhibited good microporous crystallinity. 27 The Al MAS NMR results show that 93wt% of the aluminum species are in a four-coordinated state. The Si / Al ratio of this sample is 9.3, and the specific surface area S BET 385m 2 / g, micropore volume V micro 0.17cm 3 / g.
[0111] The prepared molecular sieve is recorded as AZ6. 3 -TPD curve shows that the desorption peak temperature of the sample is 380℃.
[0112] Comparative Example 1
[0113] A ZSM-5 molecular sieve, the synthesis method of which is referred to Example 1, except that only one feeding is used to make the molar ratio of silicon source (in terms of Si content), template R, sodium aluminate (in terms of Al content), NaOH and deionized water in the reaction system be 40:5:8:1.2:2460, and only one crystallization is used. The obtained molecular sieve is recorded as DZ1.
[0114] The results of testing DZ1 showed that DZ1 was a pure phase MFI structure; its Si / Al ratio was 22, the crystallinity was low, and the specific surface area S BET 298m 2 / g, micropore volume V micro 0.15cm 3 / g, the specific surface area and micropore volume are both low, and the morphology is irregular. 27 Al MAS NMR results show that 89wt% of the aluminum species are in a tetracoordinated state. 3 -TPD curve shows that the desorption peak temperature of the sample is 330℃.
[0115] Comparative Example 2
[0116] A method for synthesizing a molecular sieve, referring to Example 1, differs only in that only one feeding is used to make the molar ratio of silicon source (in terms of Si content), template R, sodium aluminate (in terms of Al content), NaOH and deionized water in the reaction system be 40:5:8:1.2:2460, only one crystallization is used, the obtained molecular sieve is treated with a 5% by mass NaOH aqueous solution in a water bath at 80°C for 30 minutes, the sample is subjected to in-situ aluminum supplementation and desiliconization, and then filtered, washed, and dried in an oven at 100°C for 2 hours. The obtained sample is recorded as DZ2.
[0117] The results of testing DZ2 showed that DZ2 was a pure phase MFI structure; its Si / Al ratio was 12, the relative crystallinity was 65%, and the specific surface area was S BET 276m 2 / g, micropore volume V micro 0.08cm 3 / g, the specific surface area and micropore volume are both low, and the morphology is irregular. 27 Al MAS NMR results show that 91wt% of the aluminum species are in a tetracoordinated state. 3 -TPD curve shows that the desorption peak temperature of the sample is 507℃.
[0118] Catalytic performance evaluation
[0119] The ZSM-5 molecular sieves prepared in the examples and comparative examples were made into catalysts, and their catalytic performance was tested.
[0120] The ZSM-5 molecular sieve prepared in each embodiment and comparative example is shaped into φ1mm×1mm particles; 800g is weighed, mixed evenly with 8g of an active component solution with a mass concentration of 5%, and then allowed to stand and impregnate for 12h at room temperature; the impregnated molecular sieve is then transferred to an oven and dried at a temperature of 110°C for 3h; the dried molecular sieve is then calcined at a temperature of 500°C for 3h in an air atmosphere to obtain a catalyst.
[0121] Take 5g of each of the above catalysts and load them into a stainless steel fixed bed tubular reactor, and reduce them with pure hydrogen. The reduction conditions are as follows: hydrogen flow rate 80mL / min, heating to 180℃ at 2℃ / min and keeping constant temperature for 2h, then heating to 375℃ at 2.5℃ / min and keeping constant temperature for 2h. Add raw material trimethylbenzene for selective dealkylation reaction, and the product is analyzed by HP6890 gas chromatography. Reaction conditions: reaction temperature 375℃, reaction pressure 0.6MPa, raw material weight space velocity 3.35h -1 , hydrogen to oil molar ratio 3. The statistics of the online 100h reaction results are shown in Table 1.
[0122] Activity (conversion rate C) and BTX selectivity (yield of high-quality low-carbon aromatics) are used as catalyst performance evaluation indicators.
[0123]
[0124] (TMB stands for trimethylbenzene, including 1,2,4-trimethylbenzene, 1,3,5-mesitylene and mixtures)
[0125] S BTX =(BTX in product / Σproduct)×100%
[0126] (B stands for benzene, T stands for toluene, and X stands for xylene)
[0127] Table 1
[0128]
[0129]
[0130] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.
Claims
1. A ZSM-5 molecular sieve, characterized in that: The Si / Al ratio of the ZSM-5 molecular sieve is less than 10, and the relative crystallinity is greater than 80%.
2. The ZSM-5 molecular sieve according to claim 1, characterized in that The acid strength of the ZSM-5 molecular sieve is shown as a desorption peak temperature of 360-500° C. during temperature-programmed ammonia desorption; And / or, in the ZSM-5 molecular sieve, the content of framework aluminum accounts for more than 80wt% of the total aluminum; And / or, the specific surface area S of the ZSM-5 molecular sieve BET ≥350m 2 / g, micropore volume V micro >0.15cm 3 / g.
3. A method for preparing a ZSM-5 molecular sieve, characterized in that: include: S1. Obtaining a colloid comprising a silicon source, a first aluminum source, an alkali source, a template R and a solvent I; the molar ratio of the silicon element in the silicon source to the aluminum element in the first aluminum source is greater than 10, preferably greater than 15; S2. crystallizing the colloid obtained in step S1 to obtain a slurry; S3. Adding a second aluminum source to the slurry obtained in step S2 so that the molar ratio of silicon to aluminum in the entire reaction system is less than 10; S4. Performing secondary crystallization to obtain the ZSM-5 molecular sieve; Optionally, the method further comprises S5. calcining the ZSM-5 molecular sieve once, then performing ion exchange, and then performing a second calcination.
4. The preparation method according to claim 3, characterized in that: The first aluminum source and the second aluminum source are the same or different, and are independently selected from at least one of aluminum hydroxide, aluminum isopropoxide, aluminum sec-butoxide, sodium aluminate, aluminum sulfate, aluminum nitrate, aluminum chloride, and aluminum oxide; Preferably, the second aluminum source is selected from at least one of aluminum isopropoxide, aluminum sec-butoxide, sodium aluminate, aluminum sulfate, aluminum nitrate, and aluminum chloride.
5. The preparation method according to claim 3 or 4, characterized in that: The alkali source includes alkali metal hydroxide and / or ammonia water; preferably, the alkali metal includes at least one of Li, Na, K, Rb, and Cs; And / or, the silicon source includes at least one of silicon powder, silicon balls, silica gel, silica sol, sodium silicate, silica alumina, silicate, silicon tetrachloride, silane, white carbon black, and diatomaceous earth; preferably, the silane is selected from at least one of tetramethylsilane, methyltrimethoxysilane, isobutylene triethoxysilane, trichlorosilane, and tetraethoxysilane; and / or, the template R comprises at least one of ammonia water, piperidine, N,N,N-trimethyl-1-adamantyl ammonium bromide, pyridine, cyclopropylamine, ethylamine, diethylamine, triethylamine, propylamine, dipropylamine, tripropylamine, n-butylamine, tetrapropylammonium hydroxide, tetraethylammonium hydroxide, tetramethylammonium hydroxide, tetrapropylammonium iodide, tetrapropylammonium bromide, tetraethylammonium bromide, tetraethylammonium chloride or tetramethylammonium chloride; And / or, the solvent I includes at least one of deionized water, alcohol solvents, and imidazole-type ionic liquids; preferably, the solvent I includes at least one of deionized water, methanol, ethanol, isopropanol, ethylene glycol, glycerol, acetone, and n-butanol.
6. The preparation method according to any one of claims 3 to 5, characterized in that: The molar ratio of the alkali source to the silicon element in the silicon source is: OH - / Si=0.01~0.45; And / or, the molar ratio of the solvent I to the silicon element in the silicon source is: I / Si=5-50; And / or, the molar ratio of the template R to the silicon element in the silicon source is: R / Si=0.001-0.
55.
7. The preparation method according to any one of claims 3 to 6, characterized in that: The ion exchange comprises ammonium exchange; Preferably, The ammonium exchange reagent includes at least one of ammonium nitrate, ammonium chloride, ammonium oxalate and ammonium sulfate; And / or, the ammonium exchange is carried out at a temperature of 10 to 120° C. for 0.1 to 1000 h; and / or, the concentration of the aqueous solution of the ammonium exchange reagent is 0.01 to 5 mol / L; And / or, the volume mass ratio of the aqueous solution of the ammonium exchange reagent to the ZSM-5 molecular sieve is 4-10 mL:1 g.
8. The preparation method according to any one of claims 3 to 7, characterized in that: The number of ion exchanges is 1 to 20 times; And / or, after the ion exchange, filtering, washing and drying are first performed, and then secondary calcination is performed; preferably, the drying temperature is 30 to 200° C.; And / or, the stirring speed of the primary crystallization is 0 to 6000 rpm, the crystallization temperature is 80 to 200° C., and the crystallization time is 2 to 2000 hours; And / or, the stirring speed of the secondary crystallization is 0 to 6000 rpm, the crystallization temperature is 80 to 200° C., and the crystallization time is 2 to 2000 hours; And / or, after the secondary crystallization, the method further comprises filtering, washing and drying steps; preferably, the drying temperature is 30 to 200° C.; And / or, the primary calcination temperature is 200-980° C., and the primary calcination time is 0.1-250 h; And / or, the temperature of the secondary calcination is 400-650° C., and the time of the secondary calcination is 1-10 hours.
9. Use of the ZSM-5 molecular sieve according to claim 1 or 2 or the ZSM-5 molecular sieve prepared by the preparation method according to any one of claims 3 to 8 in aromatic hydrocarbon conversion.
10. An aromatic hydrocarbon conversion catalyst, characterized in that: The catalyst comprises the ZSM-5 molecular sieve described in claim 1 or 2 or the ZSM-5 molecular sieve prepared by the preparation method described in any one of claims 3 to 8.
Citation Information
Patent Citations
Gradient acid distributed ZSM-5 molecular sieve and preparation method thereof
CN102910646A
Synthetic method of ZSM-5 type molecular sieve
CN103848439A
In-situ aluminum-replenishing modification method for ZSM-5
CN107226474A
Method for synthesizing MFI type molecular sieve with low silica-alumina ratio
CN111252783A
Single-crystal aluminum-rich stepped-pore HZSM-5 molecular sieve and green preparation method of single-crystal aluminum-rich stepped-pore HZSM-5 molecular sieve
CN112591764A
Cited By
Diesel hydrocracking catalyst and preparation method and application thereof
CN119897149A
Molecular sieve acid site setting simulation method, equipment and medium
CN120636586A
Method and system for producing light aromatic hydrocarbon and olefin from diesel oil and application
CN121226114A